COMPARATIVE ANALYSIS OF LIFESTYLE AND PURCHASING DECISIONS ON THE SHOPEE MARKETPLACE: A STUDY OF MALANGKUCECWARA COLLEGE STUDENTS - Nunung Nurastuti Utami (International Journal of Social Science, 2026)
This study aims to analyze differences in lifestyle and purchasing decisions on the Shopee marketplace between male and female students. Using an independent sample t-test, the results of the t-values ​​on lifestyle and purchasing decisions between male and female students were 1.116 (sig: 0.27) and -2.780 (sig: 0.007), respectively. This indicates that there is no difference in lifestyle between male and female students, but there is a difference in purchasing decisions on the Shopee marketplace between male and female students.Based on the research findings, it is recommended that lifestyle policies should not be treated differently; however, to improve purchasing decisions, a specific strategy for student purchases is needed. Further research is needed to examine factors related to the lifestyle and purchasing decisions of male and female students using different analysis methods.